A framework for marketing management - Kotler, Philip; Keller, Kevin Lane (Upper Saddle River, N.J. : Prentice Hall, 2012)
Building on the broad theme of holistic marketing, this edition explores the vital role of creativity and innovation in successful marketing. Other major themes include customer value creation, marketing ethics and social responsibility, and marketing accountability. Another key theme is the impact of technology on contemporary marketing, driving developments as diverse as podcasts and marketing dashboards.
"'The fifth edition of A framework for marketing management' is a concise paperback adapted from Philip Kotler and Kevin Lane Keller's fourteenth edition of 'Marketing management'"--Preface.
Includes bibliographical references and index.
oif 08/05/13
Loans
Keywords: Marketing; Marketing management